2000
DOI: 10.1111/j.1528-1157.2000.tb00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Knowledge, Attitude, and Practice of Epilepsy in Kerala, South India

Abstract: Summary:Purpose: To ascertain the prevalence and pattern of epilepsy and to characterize and quantify knowledge, attitude, and practice (KAP) toward epilepsy among the people of the state of Kerala, which is distinguished from the rest of India by a high level of literacy and health awareness of its population.Methods: We conducted a door-to-door survey covering the entire population of 238, I02 people residing in 43,68 I households in a seniiurban area of central Kerala. The screening questionnaire administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
175
7
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(217 citation statements)
references
References 36 publications
30
175
7
5
Order By: Relevance
“…It has been clearly observed that the level of education infl uences the answers about the disease and leads to less pejorative attitudes to persons with epilepsy, corroborating with other researches designed for similar purposes 4,[6][7][8][9][10][11][13][14][15] . It is inferred that populations with a lower level of education and a lower income probably also have less access to information concerning epilepsy and this contributes to maintaining erroneous concepts about the disease.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It has been clearly observed that the level of education infl uences the answers about the disease and leads to less pejorative attitudes to persons with epilepsy, corroborating with other researches designed for similar purposes 4,[6][7][8][9][10][11][13][14][15] . It is inferred that populations with a lower level of education and a lower income probably also have less access to information concerning epilepsy and this contributes to maintaining erroneous concepts about the disease.…”
Section: Discussionsupporting
confidence: 62%
“…Questionnaires that evaluate the perception of epilepsy in many different social segments have been used by a great number of authors [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . Although many limitations have been observed such as understanding the questions, diffi culty in achieving the right answer since there is a broad range of epilepsies, the tendency is to not expose negative positions on the subject and the non-validation of the instrument 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 90% of our patients expressed that society especially discriminated women with epilepsy. In a recently conducted populationbased knowledge, attitude, and practice survey in central Kerala, 39% of the respondents felt that epilepsy is a hindrance to married life (Radhakrishnan et al, 2000). Furthermore, until recently, an Indian law equated epilepsy with insanity as a ground for divorce (Mani, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…5 Sociocultural aspects of epilepsy appears also to affect depression. [6][7][8] Some of the antiepileptic drugs (AEDs) may cause depression. 9 Other factors, such as seizure frequency, degree of seizure freedom and duration of epilepsy, have been shown to considerably contribute to the prevalence of depression among PWE [10].…”
Section: Introductionmentioning
confidence: 99%